2021
DOI: 10.24996/ijs.2021.62.11(si).28
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Sustainable City in Iraq Using SAM Program to Calculate Renewable Energy

Abstract: Urban design and human activity are main causes of environmental pollution and climate change, such as reliance on energy production plants, factories and transportation that depend on fossil fuels, in addition to transformation of most green areas into residential areas. This paper aims to establish a sustainable city with an environment friendly urban design that contributes to exploitation of natural resources in the generation of electric power, use of green means of transport and thus the reduction of pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Furthermore, the simulation determined that the optimal PV system capacity for meeting the electrical demand in Baghdad was 5 kW, with a battery capacity of 10 KW and an inverter capacity of 5 kW. It also found that the cost of the PVbattery system, including the initial capital investment, present cost of components, and balance of system costs, could be completely offset by the electricity generated by the system and even result in a profit [20].…”
Section: Results Of the Baghdad Hybrid Pv-battery Studymentioning
confidence: 99%
“…Furthermore, the simulation determined that the optimal PV system capacity for meeting the electrical demand in Baghdad was 5 kW, with a battery capacity of 10 KW and an inverter capacity of 5 kW. It also found that the cost of the PVbattery system, including the initial capital investment, present cost of components, and balance of system costs, could be completely offset by the electricity generated by the system and even result in a profit [20].…”
Section: Results Of the Baghdad Hybrid Pv-battery Studymentioning
confidence: 99%
“…The authors suggest that the use of machine learning models for wind speed prediction can help to improve the efficiency and profitability of wind energy systems by enabling more accurate forecasting and better decision-making. Al-Swaiedi et al [9] focuse on the design of a sustainable city in Iraq and the use of the system advisor model (SAM) program to calculate renewable energy potential. The results show that a combination of solar and wind energy can be used to meet the energy demand of the city, with the potential to generate a significant amount of renewable energy.…”
Section: Introductionmentioning
confidence: 99%